On the accuracy of T1 mapping: Searching for common ground - Stikov, Nikola; Boudreau, Mathieu; Levesque, Ives R.; Tardif, Christine L.; Barral, Joëlle K.; Pike, G. Bruce (Magnetic resonance in medicine, 2015)
Purpose There are many T1 mapping methods available, each of them validated in phantoms and reporting excellent agreement with literature. However, values in literature vary greatly, with T1 in white matter ranging from 690 to 1100 ms at 3 Tesla. This brings into question the accuracy of one of the most fundamental measurements in quantitative MRI. Our goal was to explain these variations and look into ways of mitigating them. Theory and Methods We evaluated the three most common T1 mapping methods (inversion recovery, Look‐Locker, and variable flip angle) through Bloch simulations, a white matter phantom and the brains of 10 healthy subjects (single‐slice). We pooled the T1 histograms of the subjects to determine whether there is a sequence‐dependent bias and whether it is reproducible across subjects. Results We found good agreement between the three methods in phantoms, but poor agreement in vivo, with the white matter T1 histogram peak in healthy subjects varying by more than 30% depending on the method used. We also found that the pooled brain histograms displayed three distinct white matter peaks, with Look‐Locker consistently underestimating, and variable flip angle overestimating the inversion recovery T1 values. The Bloch simulations indicated that incomplete spoiling and inaccurate B1 mapping could account for the observed differences. Conclusion We conclude that the three most common T1 mapping protocols produce stable T1 values in phantoms, but not in vivo. To improve the accuracy of T1 mapping, we recommend that sites perform in vivo validation of their T1 mapping method against the inversion recovery reference method, as the first step toward developing a robust calibration scheme. Magn Reson Med 73:514–522, 2015. © 2014 Wiley Periodicals, Inc.